Teaching as design. - Goodyear, Peter (HERDSA Review of Higher Education v.2 p.27-50, 2015)
This review paper draws together some ideas emerging from recent research and development activity in the field of 'design for learning'. It explores the argument that teaching in higher education will necessarily shift the balance of its efforts towards a greater investment in design, as a way of coping with otherwise intolerable pressures on staff and resources. It frames this argument by expanding the core conceptions of what teaching work entails and then focuses on some characteristic qualities of teaching as a design activity. Research relevant to 'teaching as design' intertwines issues that are of practical and theoretical significance. The scientific study of teachers' design work can be seen as falling into three main areas: design epistemology (or the study of 'designerly ways of knowing'), design phenomenology (the study of the products of the design process), and design praxiology (the study of the practices and processes of design). The paper introduces some examples of work in each of these areas and identifies areas that need further research. For practical purposes, the paper discusses ways of building design capacity within universities, through sharpening the focus on students' activity, and helping students to take greater control over the design of their own learning tasks and learning environments. [Author abstract]